The first experience of the usage of leadless pacemaker in Ukraine - O.M. Grytsay; Ya.V. Skybchyk; E.V. Zhytynskyi; V.O. Kuts; O.J. Zharinov (Кардіохірургія та інтервенційна кардіологія)
The article presents literature review about pacemakers of different generations. It is indicated that wire-type of pacemakers are accompanied by frequent local complications which are related to the system of electrodes, i.e. electrode fracture, electrode dislocation, subclavian vein thrombosis, right ventricle perforation resulting in hemopericardium, pneumothorax and infectious complications. Failure rates and technical issues are reported up to 0.1–1.5 % per year. Medtronic Micra leadless pacemaker has shown safety and efficacy at short term and during prospective monitoring as an alternative to traditional pacemakers. This technology demonstrates important perspectives in cardiac rhythm control. In Ukraine, on the basis of the Heart Institute, Ministry of Health of Ukraine, 12 successful surgical interventions were conducted using Medtronic Micra.